Analisa Pengaruh Interferensi Terhadap Passive Repeater Link Microwave Berdasarkan Stanadar ITU-T-G821 - Winda Ekaliya Rinanda; Ade Wahyudin; Alfin Hikmaturokhman (LPPM Institut Teknologi Telkom Purwokerto, 2019)
In an area that has such a high plateau area of Selawangi and has a large number of Pabuaran mountains and hills that make the occurrence of failure information submitted between BTS, the resulting failure there is a mountain Standing tall among the site Selawangi to the site Pabuaran, the mountain is called barrier (Obstacle) which resulted in the signal information submitted from site to site Selawangi Pabuaran underwent no Line Of Sight (LOS). For it is required the addition of an antenna repeaters (Repeater) for a repeat of a radio signal by changing a beam or radio without an application electronic equipment. On the research of this Repeater is used back to back because this type of antenna antenna is better to transmit the information received and will get reinforcement of gain. From the results of testing by using design software Pathloss 5.0, then the obtained results the value of reliability of systems that do not use passive Repeaterback to back i.e. availability and outage time does not appear, and by using passive Repeater also availability results do not appear, can be summed up the results of the design of the network using passive microwave Repeaters have not been successful because the results of the availability and outage time does not appear and make the results of the availability is not appropriate or approaching the standard of ITU-T-G821, therefore the author will examine further and analyze further, and will replace the device if necessary.